2005
DOI: 10.1111/j.1365-2273.2005.00978.x
|View full text |Cite
|
Sign up to set email alerts
|

How we do it: the Bradford grommet trainer: a model for training in myringotomy and grommet insertion

Abstract: Myringotomy and grommet insertion is the most common operative procedure in otological practice. We describe a simple, cheap and effective model for the junior trainee to develop the skills required for myringotomy and grommet insertion without compromising patient safety. As the materials required for our model are more readily available, it is more likely to gain widespread acceptance in ENT training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 2 publications
0
19
0
Order By: Relevance
“…Eleven different VTI simulators are described in the literature . Two models showed face validity data, three studies reported on the effect of iteration, and one included construct validity data .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eleven different VTI simulators are described in the literature . Two models showed face validity data, three studies reported on the effect of iteration, and one included construct validity data .…”
Section: Resultsmentioning
confidence: 99%
“…Eleven different VTI simulators are described in the literature. [8][9][10][11][12][13][14][15][16][17][18][19] Two models showed face validity data, 16,18 three studies reported on the effect of iteration, 14,15,19 and one included construct validity data. 15 The remainder were purely descriptive articles.…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous authors have described techniques for simulating grommet insertion; however, they fulfil only that purpose and can be difficult to re‐use. We describe a technique for simulation of an ear canal and tympanic membrane using cheap and readily available material that can be stored and re‐used on multiple occasions.…”
mentioning
confidence: 99%